Stunted upward mobility in a learning environment reduces the academic benefits of growth mindsets - Jia, Lile (Proc Natl Acad Sci U S A, 2021)
Does stunted upward mobility in an educational system impede beneficial psychological processes of learning? We predicted that growth mindsets of intelligence, a well-established psychological stimulant to learning, would be less potent in low-mobility, as compared to high-mobility, learning environments. An analysis of a large cross-national dataset and a longitudinal experiment accumulated converging evidence for this hypothesis. Study 1 examined data from 15-y-old students across 30 countries (n = 235,141 persons). Replicating past findings, growth mindsets positively predicted students’ math, science, and reading literacy. More importantly, the country-level indicator of educational mobility (i.e., the percentage of children from low-education households to graduate from tertiary education) moderated the effect of growth mindsets. Depending on the subject, the gain in predicted academic performance from a one-unit increase in growth mindsets was reduced by 42 to 45% from a high-mobility to a low-mobility country. Results were robust with or without important covariates. Study 2 experimentally manipulated people’s perception of mobility in a carefully constructed learning environment. The moderating role of educational mobility was replicated and extended to learning behavior, which subsequently predicted performance. Evidence further suggests that in high-mobility environments, both advantaged and disadvantaged learners benefited from growth mindsets, albeit likely through diverging mechanisms; when the effect of growth mindsets was attenuated in low-mobility environments, the potential for the disadvantaged to overcome the performance gap was also limited. Implications for galvanizing the upward mobility of the disadvantaged, evaluating the effectiveness of mindset interventions, and conceptualizing social mobility from a psychological perspective are discussed.